2006
DOI: 10.1111/j.1365-2141.2006.06366.x
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin treatment in advanced multiple myeloma is associated with improved immunological functions: could it be beneficial in early disease?

Abstract: SummaryErythropoietin (Epo) is the main growth regulator of red blood cells, and recombinant human erythropoietin (rHuEpo) is thus used in clinical practice for the treatment of anaemia, primarily in kidney disease and cancer. rHuEpo treatment was found to be associated with prolonged survival of multiple myeloma (MM) patients. This clinical observation was then supported by studies on murine myeloma models. It thus appeared that rHuEpo had an anti-myeloma effect, causally related to an immunomodulatory functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
1
1

Year Published

2007
2007
2009
2009

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 67 publications
4
40
1
1
Order By: Relevance
“…This phenomenon is one of the major defects of the immune system observed in MM patients. Another indicator for a possible role of EPO on DCs is the finding that, in addition to its anti-neoplastic effects in MM, EPO also has immunomodulatory effects that reduce immunosuppression in MM (Prutchi-Sagiv et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon is one of the major defects of the immune system observed in MM patients. Another indicator for a possible role of EPO on DCs is the finding that, in addition to its anti-neoplastic effects in MM, EPO also has immunomodulatory effects that reduce immunosuppression in MM (Prutchi-Sagiv et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…EPO treatment in MM patients was associated with effects on given immunological parameters and functions, including normalization of the CD4:CD8 cell ratio, as well as enhanced phytohemagglutinin-mediated T cell activation and proliferation (Prutchi-Sagiv et al, 2006).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The authors of the present study [7] could not previously detect EPOR in mouse spleen cells or in human lymphocytes by RT-PCR [11], while others described EPO binding on a B cell line [19]. Also in consideration of the lack of effect of EPO on T cell activation when whole blood cell cultures are stimulated with EPO, Katz et al [7] hypothesize that other cells, such as antigen presenting cells, might mediate the effects on B and T cells.…”
mentioning
confidence: 57%
“…The effect of EPO on MM was also reproduced in murine models, where EPO promotes the development of an effective and long-lasting anti-tumor specific immune response mediated via activated CD8 + T cells [10]. By specifically investigating EPO effects on immunological functions in advanced MM patients, a study from the same group showed that EPO increased T cell activation and proliferation, normalized the CD4:CD8 T cell ratio, decreased the percentage of CD8 + T cells expressing the inhibitory molecule CTLA-4, and increased CD8 + T cells expressing the costimulatory CD28 [11].…”
mentioning
confidence: 99%